The Role of Profitability in Moderating Political Connections, Corporate Risk, Leverage and Firm Size to Tax Avoidance: Peran Profitabilitas Dalam Memoderasi Koneksi Politik, Risiko Perusahaan, Leverage dan Ukuran Perusahaan Terhadap Penghindaran Pajak - Latifatul, Lala; Kristiana, Ida; Hanum, Ayu Noviani (Universitas Muhammadiyah Sidoarjo, 2023)
This study examines the effect of political connection, corporate risk, leverage, and firm size on tax avoidance with profitability as a moderating variable. The data used are annual financial reports of food and beverage registered in the Indonesia Stock Exchange (IDX) for the 2018-2021. The sample used was 99 companies, obtained using a purposive sampling technique. The data analysis used is Multiple Linear Regression and Moderated Regression Analisis (MRA). In this study, there is a novelty, namely the addition of profitability as a moderating variable, because, in previous studies, the use of moderation with the same independent and dependent variables was not found in this study. The result of this study shows that political connection, corporate risk, and firm size do not affect tax avoidance. Meanwhile, leverage has a significant positive effect on tax avoidance. In addition, profitability can moderate the effect of firm size on tax avoidance. However, profitability cannot moderate the effect of political connection, corporate risk, and leverage on tax avoidance. Based on these results, the implication of this study is that leverage in companies must be considered because the greater the level of corporate leverage, the lower the tax burden borne by the company so that debt becomes a management priority to avoid a larger tax burden. Therefore, the greater the leverage ratio, the greater the level of corporate tax avoidance. Likewise, profitability can moderate the effect of company size on tax avoidance must also be considered because the larger the size will enable the company to earn high profits. The firm value will also increase, so the company can control tax avoidance.